Negative Effects of Non-Tariff Trade Barriers on the Welfare of Indonesians - Felippa Amanta; Iqbal Dawam Wibisono (Center for Indonesian Policy Studies (CIPS), 2021)
High food prices have undermined Indonesia's effort to reduce poverty and improve health and nutrition indicators. It is estimated that for every 1% increase in price, the national poverty headcount rises by 1%. A significant contributor to high food prices is the prevalence of non-tariff measures (NTM) in the international trade of food and agriculture products. Some assessments have been made and they showed how the removal of non-tariff measures on food and agricultural goods would support poverty reduction and nutritional improvement. Removing non-tariff measures on rice and meat, for example, could lead to an overall reduction in poverty rate of 2.8 percent percentage points. Two moves could be considered to gain the most significant benefits from the removal of non-tariff measures: the removal of quotas and the application of automatic import licensing. The liberalisation of food trade must also be accompanied by heightened competition among importers, system improvements to facilitate import processes, and innovative agriculture policies to boost the competitiveness of domestic producers.
Keywords: 330; Non-Tariff Trade Barriers; poverty; poverty in indonesia; nutrition in indonesia; nutrition; Non-tariff Measure; Non-Automatic Licensing System; beef import; beef prices; rice prices; rice import; food prices; poverty rate; Sanitary and phytosanitary measures; Quantitative restrictions; felippa; iqbal wibisono